2014
DOI: 10.1017/s1368980014000949
|View full text |Cite
|
Sign up to set email alerts
|

Daily sodium consumption and CVD mortality in the general population: systematic review and meta-analysis of prospective studies

Abstract: Objective: The purpose of the present study was to determine whether elevated dietary Na intake could be associated with CVD mortality. Design: We performed a systematic review and meta-analysis of prospective studies representing the general population. The adjusted relative risks and their 95 % confidence intervals were pooled by the inverse variance method using random-effects models. Heterogeneity, publication bias, subgroup and meta-regression analyses were performed. Settings: MEDLINE (since 1973), Embas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 51 publications
2
59
0
Order By: Relevance
“…In keeping with the linear dose–response effect of sodium intake on blood pressure and of blood pressure on the risk of cardiovascular disease or death, 39 analyses of general population cohort studies 6,3840 or of specific groups, such as patients with chronic kidney disease, 41 support a positive linear association from low to high levels of sodium intake and an increased risk of cardiovascular disease. One analysis indicated that the rate of death from cardiovascular disease increased linearly by 1% with every 230-mg increase in daily sodium intake (4% for every 1000 mg).…”
Section: Consistencymentioning
confidence: 74%
See 2 more Smart Citations
“…In keeping with the linear dose–response effect of sodium intake on blood pressure and of blood pressure on the risk of cardiovascular disease or death, 39 analyses of general population cohort studies 6,3840 or of specific groups, such as patients with chronic kidney disease, 41 support a positive linear association from low to high levels of sodium intake and an increased risk of cardiovascular disease. One analysis indicated that the rate of death from cardiovascular disease increased linearly by 1% with every 230-mg increase in daily sodium intake (4% for every 1000 mg).…”
Section: Consistencymentioning
confidence: 74%
“…One analysis indicated that the rate of death from cardiovascular disease increased linearly by 1% with every 230-mg increase in daily sodium intake (4% for every 1000 mg). 38 This association, however, is probably attenuated by reporting and coding errors in dietary measures of sodium intake and, for urinary biomarkers, the use of one or two consecutive 24-hour urine collections. 24,25,29,38,42 Because the foods we eat vary from day to day, a person’s variability in sodium intake can be as great or greater than interpersonal variability.…”
Section: Consistencymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, although high blood pressure has remained the leading risk factor in Korea, it is closely related to the consumption of sodium 22. The sodium intake in Korea is more than double the WHO dietary recommendation and increases the risk of hypertensive disease 37…”
Section: Discussionmentioning
confidence: 99%
“…Increased dietary consumption of total vegetables; greens and beans; total fruit; whole fruit; whole grains; seafood and plant proteins; and healthful fatty acids, and the reduced consumption of sodium and empty calories has been shown to improve cardiometabolic risk in type 2 diabetes. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Limitations This study has several limitations. First, the sample size of the study was small, limiting the ability to detect significant findings in some variables.…”
Section: Discussionmentioning
confidence: 99%